Historical Development of Interdisciplinary Teaching Approaches in Social Studies Education in Turkey - Sagdic, Mustafa (KARABUK UNIV, 2019)
The object of this study is to assess the interdisciplinary teaching approach in social studies education, based on the historical development in Turkey. In the study, the curriculum programs of the Republican period, the national education council decisions and the related tebligler journals were examined with document analysis method. The study is carried out according to qualitative research techniques. The obtained documents were subjected to content analysis. Findings based on descriptive analysis technique were discussed with local and foreign literature and specific evaluations were made and some suggestions related to social studies programs were put forward. Social studies classes in primary schools in Turkey in 1962 as the first Society and Country Studies are combined in a course titled. In 1968, the name Social Studies was adopted for this course. In middle schools, this combination was realized in 1971. In 1985, the Social Studies course was removed from the middle school and replaced by National History, National Geography, and Citizenship courses. In 1998, these lessons were combined as Social Studies, covering the 4th to 7th-grade classes. In 2005, a constructivist approach was adopted and a new social studies program was announced. However, it is observed that the subjects of different disciplines cannot be adequately related to each other in the course programs until 2005 and an interdisciplinary approach cannot be implemented sufficiently. For the first time in social studies program updated in 2018, all areas of social sciences such as history, geography, law, economics, sociology, anthropology, political science, ethnography, archeology, and psychology could be handled with an interdisciplinary approach. It is suggested that the interdisciplinary approach in the future curriculum should be determined by identifying the current problems of society.
Keywords: Social studies; Curriculum; Interdisciplinary Teaching; Turkish education system; Arts & Humanities - Other Topics